2012
DOI: 10.1080/02568543.2012.686472
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Age Reading Buddies and Cultural-Sensitive Literature: Student-Centered English Language Instruction in an Ethiopian Budget School

Abstract: The Ethiopian government has called for educational improvement, emphasizing the employment of active, student-centered pedagogy. One way of maximizing an interactive learning approach involves blending a cross-age reading buddies program with high-quality, culturally relevant children's literature. Employing descriptive, mixed-method research, this study explored the effectiveness of books and buddies on English language use, motivation, and active learning in an underresourced, "budget" school in Addis Ababa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Although not explicitly carrying out an experimental study, in Ethiopia, Cianca (2012) compared the frequency of interactions between the workbooks of students who had received a ‘traditional’ approach compared to those who had participated in the ‘reading buddies’ (p. 411) programme, and reported that there were more examples of English language use in the reading buddies group. The most robustly designed quantitative studies in the review all focused on science teaching, and used larger samples to compare LCP outcomes (in the treatment groups) with traditional teacher‐centred outcomes (in the control groups).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not explicitly carrying out an experimental study, in Ethiopia, Cianca (2012) compared the frequency of interactions between the workbooks of students who had received a ‘traditional’ approach compared to those who had participated in the ‘reading buddies’ (p. 411) programme, and reported that there were more examples of English language use in the reading buddies group. The most robustly designed quantitative studies in the review all focused on science teaching, and used larger samples to compare LCP outcomes (in the treatment groups) with traditional teacher‐centred outcomes (in the control groups).…”
Section: Resultsmentioning
confidence: 99%
“…A commonly cited outcome of LCP implementation, reported by 28 studies, involved teachers becoming more positively disposed towards LCP after having taken part in an LCP‐related reform (e.g., Akello et al, 2016 in Uganda; Cianca, 2012 in Ethiopia; Wahyudi & Treagust, 2004 in Indonesia). Survey results (e.g., Isikoglu et al, 2009 in Turkey; Jennings, 2012 in Jamaica; Joong, 2012 in China) indicated that teachers had gained more favourable views of LCP over the course of implementation of an LCP‐related change.…”
Section: Resultsmentioning
confidence: 99%